APP-ASSISTED BOARDGAME AS AN EDUCATIONAL MEDIUM FOR ELEMENTARY SCHOOL’S CHILDREN'S COLLABORATIVE SKILL’S - Tegar Priskadana Putra; Alvanov Zpalanzani Mansoor (Wimba : Jurnal Komunikasi Visual, 2023)
Boardgame is one form of game that is presently popular. The development of board games is also interesting from board games which were originally just paper and boards, now they are starting to penetrate the digital world. Starting from board games that are present digitally, implementing a hybrid concept between physical and digital, to those that use the latest technology. The addition of digital tools or applications to board games seeks to enhance the playing experience by making games more exciting, fascinating and interactive. With the presence of digital media in a board game, digital media interventions such as the use of audio, video, or even interactive displays are conceivable. In addition to serving as a form of diversion, board games can also serve as an educational tool. With board games as an educational medium, tedious learning can become more enjoyable. Boardgames as learning media are not new; there are already quite a few boardgame titles that contain science and soft skills-related learning content. Students must possess four competencies in the 21st century: critical thinking and problem solving, creativity, communication skills, and problem-solving skills through collaboration. During the pandemic, many online students encountered difficulties collaborating with their classmates. There is a need for learning materials that facilitate student collaboration, and board games are one such medium. Collaboration is nothing new in the realm of collaborative education; it has become an integral part of the existing educational structure. Collaboration is an integral element of the current education system in Indonesia, which emphasises character education, and is even included in the Pancasila student profile. Based on this phenomenon and aided by a review of the relevant literature, research was conducted to determine how board games with digital media are utilised as collaborative learning media for children. It is necessary to dissect the design and concept of a board game to determine how they affect the player's experience. Based on this experience, additional research was conducted to determine what children can learn from board games with digital applications.